Teknik Alexander terhadap Tingkat Kenyamanan pada Ibu Hamil Trimester III - Weni Apriyani; Muhammad Hadi; Idriani Idriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the Alexander technique on the comfort level of pregnant women in the third trimester. This research uses a quasi-experimental design approach with a pretest-posttest design with a control group design. The paired sample t-test analysis results showed that there was a difference in the average level of comfort in the intervention group before and after being given the intervention with a p-value of 0.000. In the control group, a p-value of 0.282 was obtained. This indicates that there is no difference in the level of comfort before and after. The results of the GLM-RM test showed that the greenhouse-geisser (Sig) value was 0.000 < 0.005, and the most significant partial eta square value was in the 7th measurement (0.454). In conclusion, the alexander technique can increase comfort in third-trimester pregnant women. Keywords: Third-Trimester Pregnant Women, Comfort, Alexander Technique